INVESTMENT PORTFOLIO PERFORMANCE OPTIMIZATION OF DANA PENSIUN PERUSAHAAN PELABUHAN DAN PENGERUKAN (DP4) - Munadi, Eko
In order to minimize risk and comply with good corporate governance in pension fund industries, OJK released policy number 3/PJOK.05/2015 subject investment of pension fund, described the manageable investment types and restrict of maximum for each types for Indonesia’s pension fund, because pension funds should preserve the prudential to fulfill due date obligation. The pension fund is very restricted and regulated industries to minimize their risk, but founder and founding partners expected a good return on their investment, and it is very challenging to balance between risk and good return. Diversifications on allocating investment asset should be considerate, instead in a single asset to minimize risk. Pension fund performance indicates the return on their investment indicator is Return on Investment (RoI). During 2009-2018, RoI of pension fund industries for 2009-2018 in Indonesia still fluctuate result of their performance, with Employer Pension Fund - Defined Benefit program reached average return 10,63%. It is the highest return than the other schemes. The Indonesia Port and Dredging Company Pension Fund (DP4) is the employer pension funds in Indonesia which implements a defined benefit schemes by the founders and founding partners of PT Pelabuhan Indonesia I, II, III, IV, and Indonesia Dredging. The DP4 existing returns for past ten years 2009-2018 on average reached 6,98% with standard deviation level 5,77% from their investment portfolios. 5 (five) pension fund consist of BRI dapen, Dapen BNI, Dapen BI, Dapentel, Dapen Pertamina and Dapen PLN for benchmarking process in period 2012 to 2016. All five pension funds have the same program defined benefit scheme. On average return, the Industry reached 10,18%, JCI reached 7,49% and DP4 only reached 6,41%. The best combination proportion of Industry in a government bond, stock and corporate bond, considering their optimum portfolio return. DP4 should focus on managing investment portfolios to get optimal returns. The solution in this thesis using optimization theory from Markowitz and Solver from the Microsoft Excel add-in. To find the most optimal portfolio, an analysis of the efficient frontier curve, Capital Allocation Line (CAL), and Global Minimum Variance (GMV) would be implemented. By historical data for the past ten years, 2009 to 2018, the results of the analysis showed that DP4 achieved return 7,18% with a lower standard deviation level 3,06%. It is outperform compared to the last ten years performance and almost reached direct investment of 2017. The weight allocation for the optimal portfolio found is by allocating 10,00% of funds in deposits on call, 10,00% on time deposits, 8,00% on corporate bonds, 30,00% on Government bond, 10,00% on public stocks, 15,00% on mutual funds, 10,51% on property and 6,49% on direct placement. And Sharpe ratio increased 127,04% than ten years return.